PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SISWA PADA MATA PELAJARAN IPA BIOLOGI KELAS VII SMP NEGERI 19 PALU - Usdalifat, Sri (JSTT, 2016)
The resesearch aimed to examine the effect of inquiry learning model of the critical thinking skills and describe the effect of Inquiry Learning Model of the process skills on the Biology subject of grade VII students at SMP Negeri 19 Palu. The research method was a quasi experiment. The population was the grade VII. It was based Â random sampling and the selected class was the class VIIa with the number of students were 28 as the control class and class VIIB with the number ofÂ students were 27 as the experiment class. Retrieving data using the instrument test of the critical thinking ability and the students' skills of observation sheets. Hypothesis test process skills were analyzed by analysis of variance (ANOVA). Hypothesis test results of the critical thinking skills showed 0,001 < 0,05 and F count 31,003 > F table 4,02. Hypotheses test results of the process skills showed 0,001 < 0,05 and F count 26,666> F table was 4,02. The results of the study indicated that there were significant to the inquiry learning model critical thinking skills and also there was the effect of the process skills of the students.